(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
In the present work the interaction of methyl violet (MV) with human serum albumin (HSA) and bovine serum albumin (BSA) has been studied by the UV-denaturation method and the obtained data were compared. The denaturation parameters – denaturation temperature and denaturation interval width, were determined. It was shown that MV, binding to serum albumins, stabilizes their structure. At the same time, the stabilization degree is different. It was also shown that BSA is stabilized more, than HSA, while binding to MV.